Shir, Syrien: Siedlung und Umland des 7. Jts. v. Chr. in der nördlichen Levante - Bartl, Karin (e-Forschungsberichte des DAI, 2023)
The Late Neolithic settlement of Shir is one of the few archaeological sites in Syria, where a settlement sequence for the entire 7th Millennium BC is present. The data generated between 2005 and 2010 allow detailed insights into settlement layout, architecture development, burial customs and economic basis. In addition, the findings of lithics, ceramics and objects enable comprehensive analyzes on raw materials, technologies, use concepts, and interregional contacts in the early Late Neolithic period.